Association between Clinical Profile and Short-Term Outcomes in Paediatric Guillain-Barre Syndrome - Quaderi, Humaira Rafiqa; Salauddin, Gazi; Khan, Md Abbas Uddin (Northern International Medical College Journal, 2025)
Background: Guillain-Barre Syndrome (GBS) is a leading cause of acute flaccid paralysis in children. Clinical presentation and the nature of treatment significantly influence short-term outcomes. This study aims to assess the association between the clinical profile and short-term outcomes in paediatric GBS. Objective: The objective of this study was to evaluate the association between various clinical presentations, with shortterm outcomes in paediatric Guillain-Barre Syndrome (GBS) Methods: This retrospective observational study included paediatric GBS patients (ages 6 months to 16 years) admitted to a tertiary care hospital in Bangladesh from January 2023 to December 2024. Data were collected on clinical features, electrophysiological subtype, and treatment modality. Short-term outcomes were assessed by using the Hughes GBS Disability Score during discharge and 3 months after discharge. Statistical analysis was done to find out the association between presentation, treatment, and outcomes. Results: Among 45 children the most common clinical features were ascending lower limb weakness (100%), paraesthesia (89%), cranial nerve involvement (13.3%), and respiratory failure (24.4%). 31% were ambulatory. Electrophysiological subtypes included axonal type (84.4%) and demyelinating (15.6%). IVIG was administered to 42.2% of patients in ward and in ICU, while 31% required ICU care. The disease was progressive in 38%. Good outcomes (Hughes 0-3) were found in 47% at discharge and 62.2% after 3 months. Poor outcomes at discharge were significantly associated with progressive disease (OR =1.5, 95% CI: 0.7-3.2, p=0.01) and respiratory failure (OR=1.2, 95% CI: 0.64-2.4, p=0.02). After 3-month follow-up, several factors were found to be significant. The factors were progressive disease (OR = 6.72, 95% CI: 1.75–25.76, p = 0.005), Respiratory failure (OR = 7.4, 95% CI: 1.6–34.2, p = 0.01), respiratory tract infection as a preceding illness (OR = 3.5, 95% CI: 1.0–12.6, p=0.04) and Need for IVIG (OR=4.58 (95% CI: 1.26–16.63, p = 0.02). Conclusion: The presence of progressive disease, respiratory failure, a history of preceding respiratory infection, and those who required intravenous immunoglobulin (IVIG) therapy were found to be significant indicators of poor outcome. Early identification and aggressive management of these risk factors are crucial for improving paediatric GBS outcomes. Northern International Medical College Journal Vol. 16 No. 1-2 July 2024-January 2025, Page 721-727